The sense of time in Fitzgerald's "The Great Gatsby" - Tala’t A. Qadawi (آداب الرافدين, 1989)
This paper studies The sense of time in Fitzgerald's "The Great Gatsby" . It tackles the view of the writer who reject the present tense becuase he lives in the past.